Distribuição espaço-temporal do Aedes (Stegomyia) aegypti (Diptera: Culicidae) e casos de dengue e avaliação de variáveis climáticas em Porto Alegre (RS) - Danielle Andreza da Cruz Ferreira (2015)
Dengue is the most important arboviral that affects humans. In Brazil, the vector Aedes aegypti is distributed throughout the territory and the disease is spreading to colder areas of the country. The present study evaluated the effect of meteorological variables on the abundance of Ae. aegypti and dengue cases, and the relation between vector and cases in a subtropical humid climate of Brazil. Furthermore, we analyzed space-time distribution of the disease and vector. This study was divided in two chapters, the first evaluated the effect of temperature, precipitation and humidity on Ae. aegypti population density and dengue cases, in addition to the correlation between number of dengue cases and abundance of vector. The results suggested that precipitation has no effect on dengue incidence and Ae. aegypti abundance. It was noted that the positivity of breeding sites, females and dengue cases increased with temperature elevation. However, Ae. aegypti abundance decreased in high humidity. The best predictors were monthly mean temperature (lag = 1 month) for the positivity of breeding sites, weekly mean temperature (lag = 4 weeks, non-linear effect) for adult vector abundance and weekly minimum temperature (lag = 4 weeks) for dengue cases. Adult Ae. aegypti abundance increased with the rise of temperature until 23ºC, and stabilized afterwards. Adult vector abundance (lag = 1 week) was a positive predictor for the number of dengue cases. In second chapter we analyzed the space-time distribution of the disease and vector, also the overlap between of high vector infestation areas and dengue cases. Space-time scanning and Kernel density estimator identified several regions in the municipality with high vector infestation, but only one high dengue incidence region. Some regions were identified as high infestation areas for both Ae. aegypti larvae and adults. Space-time clusters of dengue cases and vector occurred in the hottest time of the year. There was spatial overlap between dengue cases and female Ae. Aegypti clusters, but they did not overlap in time. Understanding the distribution of the disease and Ae. aegypti and also the effect of climate on vector seasonal fluctuation scan generate relevant information for dengue Control Program in Porto Alegre.